2022
DOI: 10.3389/fcimb.2022.933523
|View full text |Cite
|
Sign up to set email alerts
|

Deep metagenomic characterization of gut microbial community and function in preeclampsia

Abstract: Preeclampsia (PE) is a pregnancy complication characterized by severe hypertension and multiple organ damage. Gut microbiota has been linked to PE by previous amplicon sequencing studies. To resolve the PE gut microbiota in a higher taxonomy resolution, we performed shotgun metagenomic sequencing on the fecal samples from 40 early-onset PE and 37 healthy pregnant women. We recovered 1,750 metagenome-assembled genomes (representing 406 species) from the metagenomic dataset and profiled their abundances. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 78 publications
(119 reference statements)
1
10
0
Order By: Relevance
“…Among the biomarkers of preeclampsia, a significant downregulation of the KEGG pathways of folate metabolism, the metabolism of cofactors and other vitamins, pyridoxal-P biosynthesis, riboflavin metabolism, and cobalamin biosynthesis was found. Conversely, the microbiota resulted in an enrichment of the species belonging to the genera Blautia, Pauljensenia, Ruminococcus, and Collinsella [153].…”
Section: Discussionmentioning
confidence: 99%
“…Among the biomarkers of preeclampsia, a significant downregulation of the KEGG pathways of folate metabolism, the metabolism of cofactors and other vitamins, pyridoxal-P biosynthesis, riboflavin metabolism, and cobalamin biosynthesis was found. Conversely, the microbiota resulted in an enrichment of the species belonging to the genera Blautia, Pauljensenia, Ruminococcus, and Collinsella [153].…”
Section: Discussionmentioning
confidence: 99%
“…Once the flora is out of balance, the balance will be destroyed, and inflammatory factors will increase, which will damage vascular endothelial cells, and then affect the stability of the blood system. Bacteroides , Bifidobacterium, and Lachnospiraceae have been proven to be related to the inflammatory-immune response mediated by intestinal flora ( Miao et al, 2021 ; Huang et al, 2022 ; Lv et al, 2022 ). In addition, dyslipidemia and renal dysfunction are also important factors affecting the occurrence and development of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that IMC treatment decreased the genus Phocacecola . It was recently shown that Phocaeicola might be related to preeclampsia occurrence [ 26 ], while currently there is a lack of information regarding its link with hypertension.…”
Section: Discussionmentioning
confidence: 99%